(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND To ensure ethical oversight, researchers wanting to conduct “research” involving human beings are typically required to obtain prior approval from an independent ethics committee. However, it can sometimes be unclear if a project needs to be submitted for ethics approval. Swiss researchers can contact research ethics committees via a “jurisdictional inquiry” for clarification whether a project needs to be submitted for ethics approval. AIMS OF THE STUDY (1) To examine the characteristics of Swiss jurisdictional inquiries, and (2) to identify possible uncertainties regarding the correct interpretation of existing legislation in Switzerland. METHODS All jurisdictional inquiries submitted to Swiss research ethics committees between July and December 2017 were reviewed using qualitative content analysis. We then conducted an online survey between June 2018 and July 2018 with all researchers who had submitted a jurisdictional inquiry including a descriptive quantitative analysis. RESULTS The review included 271 jurisdictional inquiries. Analysis identified three groups of jurisdictional inquiries: 80.4% (218/271) sought clarification whether the project had to be submitted for ethical approval; 18.5% (50/271) requested a “declaration of no objection”; and 1.1% (3/271) asked for a clarification about which of the two ordinances was applicable to the project. Analysis identified eight distinct legal issues that appeared to be the main cause for a number of jurisdictional inquiries, with the two most frequently identified issues being whether the project will produce generalisable knowledge, and whether the project uses fully anonymised data. Overall, research ethics committees decided that 78.6% (213/271) of the jurisdictional inquiries were outside their jurisdiction and did not require ethical approval, and that 15.6% required submission for ethical approval. The online survey achieved a 56.8% response rate. The majority of respondents (94/166; 56.6%) reported that all the questions they were asked during the submission of the jurisdictional inquiry were easy to understand. Respondents reported that 88% (147/166) of all projects were started or planned to start. The vast majority (154/166; 93%) of respondents also agreed with the decisions made by the research ethics committee. CONCLUSIONS Jurisdictional inquiries are an important means for researchers to clarify whether their project requires ethical oversight. However, this mixed-methods study has identified some difficulties in the interpretation of legal terms, which often reflect persistent structural issues that many other countries also face. More detailed guidance may be helpful to reduce the researchers’ uncertainties and ethics committees’ workloads in relation to jurisdictional inquiries.